Systemic Diagnosis-Based Organizational Psychology Interventions and Development Strategies in Improving Retirement Readiness - Arsi, Gardarias Aulia; Sami'an, Sami'an (Riwayat: Educational Journal of History and Humanities, 2025)
This research aims to design organizational psychology interventions aimed at improving employee retirement readiness through systemic approaches and structured development strategies. The process begins with the initial identification of problems and the preparation of an intervention agreement between the researcher and the company. This step is followed by the introduction of relevant work units and discussions with stakeholders to strengthen the understanding of the organizational context. The findings show that retirement is an important phase in employees' lives that is often accompanied by anxiety and uncertainty, especially if it is not accompanied by mental, emotional, financial, and social support. Although companies already have a retirement preparation program in place, most employees do not yet feel fully prepared for the transition. Therefore, the interventions designed in this study are focused on strengthening career planning and post-work life through activities such as financial seminars, entrepreneurship training, group counseling, and field visits.